FUNDC2 regulates platelet activation through AKT/GSK-3β/cGMP axis. Issue 11 (21st December 2018) - Ma, Qi; Zhang, Weilin; Zhu, Chongzhuo; Liu, Junling; Chen, Quan
Abstract: Aims: AKT kinase is vital for regulating signal transduction in platelet aggregation. We previously found that mitochondrial protein FUNDC2 mediates phosphoinositide 3-kinase (PI3K)/phosphatidylinositol-3, 4, 5-trisphosphate (PIP3)-dependent AKT phosphorylation and regulates platelet apoptosis. The aim of this study was to evaluate the role of FUNDC2 in platelet activation and aggregation. Methods and results: We demonstrated that FUNDC2 deficiency diminished platelet aggregation in response to a variety of agonists, including adenosine 5′-diphosphate (ADP), collagen, ristocetin/VWF, and thrombin. Consistently, in vivo assays of tail bleeding and thrombus formation showed that FUNDC2-knockout mice displayed deficiency in haemostasis and thrombosis. Mechanistically, FUNDC2 deficiency impairs the phosphorylation of AKT and downstream GSK-3β in a PI3K-dependent manner. Moreover, cGMP also plays an important role in FUNDC2/AKT-mediated platelet activation. This FUNDC2/AKT/GSK-3β/cGMP axis also regulates clot retraction of platelet-rich plasma. Conclusion: FUNDC2 positively regulates platelet functions via AKT/GSK-3β/cGMP signalling pathways, which provides new insight for platelet-related diseases. Graphical Abstract: